Psychological Theory of Activity’ Contribution to the Development of Subject-Oriented Psychophysics - Gusev, Alexey N.; Skotnikova, Irina G. (Vestnik Moskovskogo universiteta. Seriia XIV, Psikhologiia, 2023)
Background and objective. The authors present the results of their theoretical and experimental research in the field of subject-oriented psychophysics, carried out in different years in line with the subject-oriented activity and the system-oriented activity approaches. The results obtained substantiate the productivity and prospects of the A.N. Leontiev’s psych ological theory of object activity ideas as one of the important theoretical and methodological foundations of domestic psychophysical research. The principal role of the concept of a sensory task as a cognitive task of a special kind is emphasized. Such tasks of detection, discrimination, and identification of sensory signals by a person are characterized by goals accepted as these tasks’ components and by a high level of uncertainty. Therefore, these tasks require researchers to meaningfully analyze the psychological structure of the corresponding sensory process in the context of the requirements of the task being solved and in an inextricable relationship with various manifestations and internal content of human activity. The significance of the task as the goal and conditions of the subject’s activity, has appeared not only in empirical research results, but in the mathematical model of decision making and confidence in threshold-like tasks, as well. Conclusions. The results obtained convincingly prove the role of the sensory task characteristics related with individual psychological peculiarities of a subject of sensory measurements, his (her) functional states and reflective experiences as important factors determining a choice of sensory performance tools, and its effectiveness.